Bibliography. (Lope de Vega & the Comedia de Santos, 2000)
The sources cited within this issue are presented including "The Spirit of Catholicism," by Karl Adam, "Historia critica de la literatura española," by José Amador de los Ríos and "The Spanish Sacramental Plays," by Ricardo Arias.